Lessons learned from screening potential other effective area‐based conservation measures - Carly N. Cook; Madhu Rao; Peter J. Clyne; Vanessa Rathbone; Christian Barrientos; Antonio Boveda; Alex Diment; Jorge Parra; Valeria Falabella; Matthew Linke; Deo Kujirakwinja; Stephane Ostrowski; et al. (Conservation Biology, 2026)
Other effective area‐based conservation measures (OECMs) are sites that deliver effective biodiversity outcomes irrespective of their management objectives. These areas are widely expected to play an important role in efforts to protect 30% of Earth by 2030. Despite general guidance to support screening sites against the formal criteria to be OECMs, progress recognizing sites has been limited. To advance the ability to identify OECMs, we developed a questionnaire that translates the components of the broad formal guidance into statements that experts can use to screen potential OECMs. Twenty‐eight local experts used the questionnaire to evaluate a large global sample of 81 sites. Most sites evaluated were largely in good condition and had the potential to achieve conservation outcomes, but none met the criteria to be considered OECMs. The most common challenges are related to threat management, adequate resourcing, and the ability to demonstrate that governance and management are achieving effective and sustained conservation outcomes. Based on the formal International Union for Conservation of Nature guidance, sites that only partially meet the relevant criteria remain candidate OECMs. Our questionnaire provides a nuanced way to assess OECMs that can help identify what support sites need to meet the necessary criteria. With effective long‐term conservation outcomes unable to be demonstrated for so many important conservation areas, our findings raise important questions about how to ensure area‐based conservation promotes positive and sustained outcomes for biodiversity.

Project Psyche: reference genomes for all Lepidoptera in Europe - Charlotte J. Wright; Niklas Wahlberg; Roger Vila; Marko Mutanen; Pável Matos-Maraví; Kay Lucek; Irena Kleckova; Leonardo Dapporto; Vlad Dincă; Claudia Bruschini; Christopher W. Wheat; Marta Vila; et al. (Trends in Ecology & Evolution, 2025)

Autonomous methane seep site monitoring offshore western Svalbard: hourly to seasonal variability and associated oceanographic parameters - Knut Ola Dølven; Bénédicte Ferré; Anna Silyakova; Pär Jansson; Peter Linke; Manuel Moser (Ocean Science, 2022)
Improved quantification techniques of natural sources are needed to explain variations in atmospheric methane. In polar regions, high uncertainties in current estimates of methane release from the seabed remain. We present unique 10- and 3-month time series of bottom water measurements of physical and chemical parameters from two autonomous ocean observatories deployed at separate intense seabed methane seep sites (91 and 246 m depth) offshore western Svalbard from 2015 to 2016. Results show high short-term (100–1000 nmol L−1 within hours) and seasonal variation, as well as higher (2–7 times) methane concentrations compared to previous measurements. Rapid variability is explained by uneven distribution of seepage and changing ocean current directions. No overt influence of tidal hydrostatic pressure or water temperature variations on methane concentration was observed, but an observed negative correlation with temperature at the 246 m site fits with hypothesized seasonal blocking of lateral methane pathways in the sediments. Negative correlation between bottom water methane concentration (and variability) and wind forcing, concomitant with signs of weaker water column stratification, indicates increased potential for methane release to the atmosphere in fall and winter. We present new information about short- and long-term methane variability and provide a preliminary constraint on the uncertainties that arise in methane inventory estimates from this variability.

Bewegungszeit, Belastungsintensität und Bewegungsumfang im Sportunterricht - Jennifer Breithecker; David Jaitner; Julia Lohmann; Daniel Linke; Malte Siegle; Martin Lames; Hans Peter Brandl-Bredenbeck (German Journal of Exercise and Sport Research, 2021)
Zusammenfassung Untersuchungen zu Bewegungsanteilen im Sportunterricht unter Verwendung objektiver Verfahren sind in Deutschland selten. Sie sind jedoch sowohl aus gesundheits- und trainingswissenschaftlicher als auch aus sportpädagogischer Perspektive von Interesse, um Schulsportwirklichkeit systematisch analysieren zu können. Der vorliegende Beitrag untersucht Bewegungszeit (Minuten), Belastungsintensität (Herzschläge pro Minute) und Bewegungsumfang (Meter pro Minute) im Sportunterricht am Beispiel des Unterrichtsinhalts Fußball. Im Zentrum steht die Frage, ob sich Unterschiede für die Unterrichtsdauer (Einzelstunde/Doppelstunde), das Setting (indoor/outdoor) und das Geschlecht zeigen. Insgesamt nahmen 356 Schüler*innen (247 männlich, 109 weiblich) von der fünften bis zur zehnten Jahrgangsstufe ( M Alter = 12,4 Jahre) eines Gymnasiums in Bayern an der Untersuchung teil. Zum Einsatz kamen standardisierte Beobachtungsprotokolle, Herzfrequenzmesser und ein Trackingsystem (Local Position Measurement System [LPM-System]). Die Ergebnisse zeigten, dass die relative Bewegungszeit, die Belastungsintensität und der Bewegungsumfang in Einzelstunden am höchsten waren. Die relative Bewegungszeit war outdoor etwas höher als indoor. Die durchschnittliche Herzfrequenz unterschied sich nicht nach Setting und Geschlecht. Jungen erzielten einen höheren durchschnittlichen Bewegungsumfang im Vergleich zu Mädchen. Insgesamt deuten die Ergebnisse darauf hin, dass der Sportunterricht mit dem Inhalt Fußball einen substanziellen Beitrag zum täglichen Gesundheits- und Bewegungsverhalten leisten kann.

Tidal Dynamics Control on Cold-Water Coral Growth: A High-Resolution Multivariable Study on Eastern Atlantic Cold-Water Coral Sites - Katriina Juva; Sascha Flögel; Johannes Karstensen; Peter Linke; Wolf-Christian Dullo (Frontiers in Marine Science, 2020)

Epibenthos Dynamics and Environmental Fluctuations in Two Contrasting Polar Carbonate Factories (Mosselbukta and Bjørnøy-Banken, Svalbard) - Max Wisshak; Hermann Neumann; Andres Rüggeberg; Janina V. Büscher; Peter Linke; Jacek Raddatz (Frontiers in Marine Science, 2019)

The Pelagic In situ Observation System (PELAGIOS) to reveal biodiversity, behavior, and ecology of elusive oceanic fauna - Henk-Jan Hoving; Svenja Christiansen; Eduard Fabrizius; Helena Hauss; Rainer Kiko; Peter Linke; Philipp Neitzel; Uwe Piatkowski; Arne Körtzinger (Ocean Science, 2019)
There is a need for cost-efficient tools to explore deep-ocean ecosystems to collect baseline biological observations on pelagic fauna (zooplankton and nekton) and establish the vertical ecological zonation in the deep sea. The Pelagic In situ Observation System (PELAGIOS) is a 3000 m rated slowly (0.5 m s−1) towed camera system with LED illumination, an integrated oceanographic sensor set (CTD-O2) and telemetry allowing for online data acquisition and video inspection (low definition). The high-definition video is stored on the camera and later annotated using software and related to concomitantly recorded environmental data. The PELAGIOS is particularly suitable for open-ocean observations of gelatinous fauna, which is notoriously under-sampled by nets and/or destroyed by fixatives. In addition to counts, diversity, and distribution data as a function of depth and environmental conditions (T, S, O2), in situ observations of behavior, orientation, and species interactions are collected. Here, we present an overview of the technical setup of the PELAGIOS as well as example observations and analyses from the eastern tropical North Atlantic. Comparisons to data from the Multiple Opening/Closing Net and Environmental Sensing System (MOCNESS) net sampling and data from the Underwater Vision Profiler (UVP) are provided and discussed.

Optimal allocation of Red List assessments to guide conservation of biodiversity in a rapidly changing world - Virgilio Hermoso; Stephanie Renee Januchowski‐Hartley; Simon Linke; David Dudgeon; Paulo Petry; Peter McIntyre (Global Change Biology, 2017)
The IUCN Red List is the most extensive source of conservation status assessments for species worldwide, but important gaps in coverage remain. Here, we demonstrate the use of a spatial prioritization approach to efficiently prioritize species assessments to achieve increased and up‐to‐date coverage efficiently. We focus on freshwater fishes, which constitute a significant portion of vertebrate diversity, although comprehensive assessments are available for only 46% of species. We used marxan to identify ecoregions for future assessments that maximize the coverage of species while accounting for anthropogenic stress. We identified a set of priority regions that would help assess one‐third (ca 4000 species) of all freshwater fishes in need of assessment by 2020. Such assessments could be achieved without increasing current investment levels. Our approach is suitable for any taxon and can help ensure that species threat assessments are sufficiently complete to guide global conservation efforts in a rapidly changing world.

Linked sediment and water‐column methanotrophy at a man‐made gas blowout in the North Sea: Implications for methane budgeting in seasonally stratified shallow seas - Lea Steinle; Mark Schmidt; Lee Bryant; Matthias Haeckel; Peter Linke; Stefan Sommer; Jakob Zopfi; Moritz F. Lehmann; Tina Treude; Helge Niemannn (Limnology and Oceanography, 2016)
Large quantities of the greenhouse gas methane (CH 4 ) are stored in the seafloor. The flux of CH 4 from the sediments into the water column and finally to the atmosphere is mitigated by a series of microbial methanotrophic filter systems of unknown efficiency at highly active CH 4 ‐release sites in shallow marine settings. Here, we studied CH 4 ‐oxidation and the methanotrophic community at a high‐CH 4 ‐flux site in the northern North Sea (well 22/4b), where CH 4 is continuously released since a blowout in 1990. Vigorous bubble emanation from the seafloor and strongly elevated CH 4 concentrations in the water column (up to 42 µM) indicated that a substantial fraction of CH 4 bypassed the highly active (up to ∼2920 nmol cm −3 d −1 ) zone of anaerobic CH 4 ‐oxidation in sediments. In the water column, we measured rates of aerobic CH 4 ‐oxidation (up to 498 nM d −1 ) that were among the highest ever measured in a marine environment and, under stratified conditions, have the potential to remove a significant part of the uprising CH 4 prior to evasion to the atmosphere. An unusual dominance of the water‐column methanotrophs by Type II methane‐oxidizing bacteria (MOB) is partially supported by recruitment of sedimentary MOB, which are entrained together with sediment particles in the CH 4 bubble plume. Our study thus provides evidence that bubble emission can be an important vector for the transport of sediment‐borne microbial inocula, aiding in the rapid colonization of the water column by methanotrophic communities and promoting their persistence close to highly active CH 4 point sources.

Thermal small steps staircase and layer migration in the Atlantis II Deep, Red Sea - Alaa M. A. Albarakati; Daniel F. McGinnis; Fazal Ahmad; Peter Linke; Marcus Dengler; Peter Feldens; Mark Schmidt; Radwan Al-Farawati (Arabian Journal of Geosciences, 2016)

Quantification of methane emission from bacterial mat sites at Quepos Slide offshore Costa Rica - Deniz Karaca; Tina Schleicher; Christian Hensen; Peter Linke; Klaus Wallmann (International Journal of Earth Sciences, 2014)

Seepage of methane at Jaco Scar, a slide caused by seamount subduction offshore Costa Rica - Susan Mau; Gregor Rehder; Heiko Sahling; Tina Schleicher; Peter Linke (International Journal of Earth Sciences, 2014)

New insights on the trophic ecology of bathyal communities from the methane seep area off Concepción, Chile (~36° S) - Germán Zapata‐Hernández; Javier Sellanes; Andrew R. Thurber; Lisa A. Levin; Frédéric Chazalon; Peter Linke (Marine Ecology, 2014)
Studies of the trophic structure in methane‐seep habitats provide insight into the ecological function of deep‐sea ecosystems. Methane seep biota on the Chilean margin likely represent a novel biogeographic province; however, little is known about the ecology of the seep fauna and particularly their trophic support. The present study, using natural abundance stable isotopes, reveals a complex trophic structure among heterotrophic consumers, with four trophic levels supported by a diversity of food sources at a methane seep area off Concepción, Chile (~36° S). Although methanotrophy, thiotrophy and phototrophy are all identified as carbon fixation mechanisms fueling the food web within this area, most of the analysed species (87.5%) incorporate carbon derived from photosynthesis and a smaller number (12%) use carbon derived from chemosynthesis. Methane‐derived carbon ( MDC ) incorporation was documented in 22 taxa, including sipunculids, gastropods, polychaetes and echinoderms. In addition, wide trophic niches were detected in suspension‐feeding and deposit‐feeding taxa, possibly associated with the use of organic matter in different stages of degradation ( e.g . from fresh to refractory). Estimates of Bayesian standard ellipses area (SEA B ) reveal different isotopic niche breadth in the predator fishes, the Patagonian toothfish Dissostichus eleginoides and the combtooth dogfish Centroscyllium nigrum , suggesting generalist versus specialist feeding behaviors, respectively. Top predators in the ecosystem were the Patagonian toothfish D. eleginoides and the dusky cat shark, Bythaelurus canescens . The blue hake Antimora rostrata also provides a trophic link between the benthic and pelagic systems, with a diet based primarily on pelagic‐derived carrion. These findings can inform accurate ecosystem models, which are critical for effective management and conservation of methane seep and adjacent deep‐sea habitats in the Southeastern Pacific.

Microbes, macrofauna, and methane: A novel seep community fueled by aerobic methanotrophy - Andrew R. Thurber; Lisa A. Levin; Ashley A. Rowden; Stefan Sommer; Peter Linke; Kerstin Kröger (Limnology and Oceanography, 2013)
During the discovery and description of seven New Zealand methane seep sites, an infaunal assemblage dominated by ampharetid polychaetes was found in association with high seabed methane emission. This ampharetid‐bed assemblage had a mean density of 57,000 ± 7800 macrofaunal individuals m −2 and a maximum wet biomass of 274 g m −2 , both being among the greatest recorded from deep‐sea methane seeps. We investigated these questions: Does the species assemblage present within these ampharetid beds form a distinct seep community on the New Zealand margin? and What type of chemoautotrophic microbes fuel this heterotrophic community? Unlike the other macro‐infaunal assemblages, the ampharetid‐bed assemblage composition was homogeneous, independent of location. Based on a mixing model of species‐specific mass and isotopic composition, combined with published respiration measurements, we estimated that this community consumes 29–90 mmol C m −2 d −1 of methane‐fueled biomass; this is > 290 times the carbon fixed by anaerobic methane oxidizers in these ampharetid beds. A fatty acid biomarker approach supported the finding that this community, unlike those previously known, consumes primarily aerobic methanotrophic bacteria. Due to the novel microbial fueling and high methane flux rates, New Zealand's ampharetid beds provide a model system to study the influence of metazoan grazing on microbially mediated biogeochemical cycles, including those that involve greenhouse gas emissions.

Sidescan sonar imagery of widespread fossil and active cold seeps along the central Chilean continental margin - Ingo Klaucke; Wilhelm Weinrebe; Peter Linke; Dirk Kläschen; Jörg Bialas (Geo-Marine Letters, 2012)

Local stream habitat variables predicted from catchment scale characteristics are useful for predicting fish distribution - James Mugodo; Mark Kennard; Peter Liston; Sue Nichols; Simon Linke; Richard H. Norris; Mark Lintermans (Hydrobiologia, 2006)

Enhanced resistance to Phytophthora infestans and Alternaria solani in leaves and tubers, respectively, of potato plants with decreased activity of the plastidic ATP/ADP transporter - Uwe Conrath; Christoph Linke; Wolfgang Jeblick; Peter Geigenberger; W. Paul Quick; H. Ekkehard Neuhaus (Planta, 2003)